RIOT: an Open Source Operating System for Low-end Embedded Devices in the IoT - Emmanuel Baccelli and Cenk Gündogan and Oliver Hahm and Peter Kietzmann and Martine Lenders and Hauke Petersen and Kaspar Schleiser and Thomas Schmidt and Matthias Wählisch (IEEE internet of things journal, 2018)
As the Internet of Things (IoT) emerges, compact operating systems are required on low-end devices to ease development and portability of IoT applications. RIOT is a prominent free and open source operating system in this space. In this paper, we provide the first comprehensive overview of RIOT. We cover the key components of interest to potential developers and users: the kernel, hardware abstraction, and software modularity, both conceptually and in practice for various example configurations. We explain operational aspects like system boot-up, timers, power management, and the use of networking. Finally, the relevant APIs as exposed by the operating system are discussed along with the larger ecosystem around RIOT, including development and open source community aspects.